THE STUDY OF SUBTITLING STRATEGY IN 'ALL TOO WELL' SONG TRANSLATION - Ivonda Seran; Agus Subiyanto (Universitas Wiralodra, 2023)
This study analyzes and discusses the subtitling strategies of the song translation